Participatory Epidemiology Network for Animal and Public Health: Enhancing the capacities of organizations to control major existing and emerging diseases - International Livestock Research Institute (International Livestock Research Institute, 2009)
National and international stakeholders leading the fight against HPAI and other major diseases have limited expertise and training in participatory epidemiology that would enable them to pro-actively address policies and institutional challenges that inhibit their adoption. For these reasons, a Participatory Epidemiology Network for Animal and Public Health has been established by the Africa-based International Livestock Research Institute (ILRI), a member of the Consultative Group on International Agricultural Research (CGIAR). The Food and Agriculture Organization of the United Nations (FAO), OIE, the African Union Inter-African Bureau for Animal Resources (AU-IBAR), the Royal Veterinary College (RVC), Vétérinaires Sans Frontières Belgium (VSF-B) and Veterinarians Without Borders/Vétérinaires Sans Frontières Canada (VSF-C) have partnered with ILRI to establish the network, design its strategies and implement programs for training, capacity building and institutional change.